When knowledge management matters: interplay between green human resources and eco-efficiency in the financial service industry - Moraes, Silvana de Souza [UNESP]; Chiappetta Jabbour, Charbel Jose; Battistelle, Rosane A.G. [UNESP]; Rodrigues, Jonny Mateus; Renwick, Douglas S.W.; Foropon, Cyril; Roubaud, David (Emerald, 2018)
Purpose: Drawing on the ability–motivation–opportunity theory applied to the greening of service industries, this paper aims to analyze the extent to which green human resource management plays a role in the adoption of eco-efficiency principles in the financial sector. Environmental knowledge management represents one of the key green human resource management components. Design/methodology/approach: This study conducted a survey with 178 employees working within one of the largest financial banks in Brazil, which has been investing in eco-efficiency for more than ten years. Findings: On the basis of structural equation modelling, this study has provided the following findings: Among all factors taken into consideration in this study, only environmental training positively influences eco-efficiency; training may be suffering owing to barriers associated with empowerment and teamwork; the eco-efficiency program of the studied company would get benefits if it provided more autonomy to employees; and finally, the eco-efficiency program of the studied bank could be more effective if connected with green teams. Originality/value: To date, this is the first work that relates – with empirical evidence from Brazil – GHRM and eco-efficiency in the financial service industry.
Keywords: Emerging economies; Energy management; Environmental knowledge; Financial services; Green human resource management